Digital Mammography - Bick, U.; Diekmann, F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This state-of-the-art reference book provides in-depth coverage of all aspects of digital mammography, including detector technology, image processing, computer-aided diagnosis, soft-copy reading, digital workflow, and PACS. Specific advantages and disadvantages of digital mammography in comparison to screen-film mammography are thoroughly discussed. By including authors from both North America and Europe, the book is able to outline variations in the use, acceptance, and quality assurance of digital mammography between the different countries and screening programs. Advanced imaging techniques and future developments such as contrast mammography and digital breast tomosynthesis are also covered in detail. All of the chapters are written by internationally recognized experts and contain numerous high-quality illustrations. This book will be of great interest both to clinicians who already use or are transitioning to digital mammography and to basic scientists working in the field.
Basic Physics of Digital Mammography -- Detectors for Digital Mammography -- Quality Control in Digital Mammography -- Classification of Artifacts in Clinical Digital Mammography -- Image Processing -- Computer-aided Detection and Diagnosis -- Softcopy Reading -- Digital Workflow, PACS, and Telemammography -- Digital Mammography Clinical Trials: The North American Experience -- Digital Mammography in European Population-Based Screening Programs -- Mammographic Signs of Malignancy: Impact of Digital Mammography on Visibility and Appearance -- Contrast-Enhanced Digital Mammography -- Digital Breast Tomosynthesis and Breast CT.
Keywords: Medicine; Gynecology; Radiology; Oncology; Pathology; Biophysics; Biological physics; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Biophysics and Biological Physics; Pathology; Oncology; Gynecology; Electronic books